Molecular mechanisms of dose-dependent regulation of hepatic lipid metabolism by BaP through modulation of AhR binding to XRE1 or XRE3 - Zhang, Mengdi; Lv, Xiaoli; Wang, Chaojie; Wang, Lei; Wang, Han; Wang, Xue; Du, Yulu; Li, Jun; Han, Xiuli; Fan, Lei; Hu, Yuxia; Bai, Tuya; et al. (Frontiers in Pharmacology, 2025)
Benzo[a]pyrene (BaP), a polycyclic aromatic hydrocarbon and a potent environmental pollutant, has been implicated in the dysregulation of lipid metabolism and metabolic diseases, warranting investigation into its effects on liver functions, particularly regarding fibroblast growth factor 21 (FGF21) mediated pathways. This study aimed to elucidate the effects of BaP on liver lipid metabolism and FGF21 expression via the aryl hydrocarbon receptor (AhR), with a focus on the regulatory interactions between BaP and xenobiotic response elements (XRE) within the promoter region of FGF21. Utilizing HepG2 cells, lipid accumulation was assessed through Oil Red O and Nile Red staining, while the expression of FGF21 protein was quantified by Western blotting and immunofluorescence techniques. Additionally, various truncated plasmids of the FGF21 promoter were synthesized for a dual-luciferase reporter assay to determine the relative luciferase activity and the modulation of FGF21 expression by BaP. The results revealed dose-dependent effects of BaP on lipid metabolism; specifically, low concentrations of BaP upregulated FGF21 expression by enhancing promoter activity in regions containing the XRE1 sequence, whereas higher BaP concentrations downregulated FGF21 expression via inhibition of promoter activity in regions with the XRE3 sequence. In conclusion, low doses of BaP facilitate AhR binding to XRE1, promoting FGF21 expression, while high doses disrupt this interaction through XRE3, culminating in decreased expression levels. These findings suggest a nuanced role of BaP in lipid metabolism regulation, with potential implications for understanding metabolic disorders associated with environmental pollutants. The study elucidates the relationship between AhR and FGF-21, providing an experimental basis for the search of new targets for the prevention and treatment of nonalcoholic fatty liver disease (NAFLD).